Rethinking music and gender: of Alick Macheso and Lady Squanda music. - Chaya, Vasco (Midlands State University, 2017)
The study explores how both men and women are framed in the music of two contemporary artistes in Zimbabwe— that is Alick Macheso and Lady Squanda. The specific objectives were to determine how men and women are framed in the music of Lady Squanda and Macheso. Grounded in the cultural studies research tradition, the study utilises the qualitative research approach. Purposively selected songs were subjected to critical discourse analysis. In-depth interviews were also conducted with the two musicians. The study established that women are framed as sex objects and powerless (symbolically annihilation of women) while men as strong and powerful in the music of Alick Macheso. However Lady Squanda a female Zimdancehall artiste tries to challenge patriarchy through her music and thus positively frames women as equally strong and violent as men.